AlTi4B2 alloy for electrical components, and preparation method and application of AlTi4B2 alloy

By developing a new AlTi4B2 alloy, the problem that existing aluminum alloys cannot meet the high temperature and corrosion resistance requirements of electrical components in high temperature and harsh environments is solved, and efficient preparation technology and excellent electrical performance are achieved.

CN119410963APending Publication Date: 2025-02-11SHANDONG YUNXIN ALUMINUM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411553562.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-02
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing aluminum alloys cannot meet the high temperature and corrosion resistance requirements of electrical components in high temperature and harsh environments.

Method used

Develop a new AlTi4B2 alloy to ensure uniform dispersion of TiB2 and conductivity of ≥55% IACS through specific alloy composition and preparation processes, including potassium fluoroborate, potassium fluorotitanate, aluminum water and aluminum ingot ratios and feeding sequences. .

Benefits of technology

The AlTi4B2 alloy has high strength and corrosion resistance at high temperatures, can maintain stability in a strong acid and alkali environment, has excellent electrical performance, and is simple and controllable in preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410963A_ABST
    Figure CN119410963A_ABST
Patent Text Reader

Abstract

The invention discloses an AlTi4B2 alloy for an electric appliance element as well as a preparation method and application of the AlTi4B2 alloy. The invention relates to an AlTi4B2 alloy for an electric appliance element. The AlTi4B2 alloy comprises the following elements: 3.9-4.2% of Ti; 1.9% to 2.1% of B; less than or equal to 0.15% of Si; fe < = 0.1%; less than or equal to 0.05% of K; less than or equal to 0.02% of F; and the balance of Al, wherein the above-mentioned percentages are all mass percentages. The AlTi4B2 alloy is good in electrical property, has high strength at high temperature and can resist erosion of strong acid and strong alkali.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an AlTi 4 B 2 The invention discloses an alloy, a preparation method and application thereof, belonging to the technical field of alloys for electrical components. Background Art

[0002] Aluminum alloy is the most widely used type of non-ferrous metal structural material in industry. It is an alloy based on aluminum with a certain amount of other alloying elements added. It has been widely used in aviation, aerospace, automobile, machinery manufacturing, shipbuilding and chemical industries.

[0003] Different use occasions require different performance requirements for aluminum alloys. When used in electrical components, they need to have high temperature resistance and corrosion resistance, and need to be able to work stably under high temperatures and harsh environments. The electrical conductivity of existing aluminum alloys is distributed between 29-44% IACS, which cannot meet the use requirements of electrical components. To this end, the applicant has developed an AlTi alloy for electrical components. 4 B 2 Alloy is a new alloy product with wide application potential in harsh environments such as high temperature and corrosion. Summary of the invention

[0004] The present invention provides an AlTi 4 B 2 Alloy, preparation method and use thereof, AlTi 4 B 2 The alloy has good electrical properties, high strength at high temperatures, and can resist corrosion from strong acids and alkalis.

[0005] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:

[0006] AlTi for electrical components 4 B 2 The alloy comprises the following elements: Ti: 3.9-4.2%; B: 1.9-2.1%; Si≤0.15%; Fe≤0.1%; K≤0.05%; F≤0.02%; V≤0.02%; Al: balance, the aforementioned % are all mass percentages.

[0007] The above electrical components use AlTi 4 B 2 Alloy internal matrix: 1cm2 cross section, total length of oxides <1500μm; TiB2 is evenly dispersed. Electrical conductivity: ≥55%IACS. Hydrogen content: <0.15ml / 100gAl.

[0008] The prior art defines the conductivity of pure copper as 100% IACS.

[0009] The above electrical components use AlTi 4 B 2 The alloy comprises raw materials including potassium fluoroborate, potassium fluorotitanate, molten aluminum and aluminum ingot; the mass ratio of potassium fluoroborate, potassium fluorotitanate, molten aluminum and aluminum ingot is: (340-390): (350-410): (800-820): (810-830).

[0010] The AlTi obtained in this application 4 B 2 Alloy is a new alloy product. It has a wide range of application potentials in harsh environments such as high temperature and corrosion, such as aviation, automobile manufacturing, and chemical industry.

[0011] Existing Al-Ti-B alloys are mostly used for the refinement of aluminum alloy grains. 4 B 2 The alloy is different from the existing Al-Ti-B alloys and is not used for the refinement of aluminum alloy grains, but is directly used for electrical components.

[0012] The above electrical components use AlTi 4 B 2 The preparation method of the alloy comprises mixing potassium fluoroborate and potassium fluorotitanate evenly to obtain a mixed salt; adding the mixed salt in four times and adding the aluminum ingot in seven times, and the specific process is as follows;

[0013] 1) Adjust the temperature of aluminum water to 710-730°C, add the first mixed salt to stir and react, increase the temperature, add the first aluminum ingot to control the temperature of the reaction process not exceeding 760°C, and dump the acid water slag (potassium fluoroaluminate) after the reaction is completed;

[0014] 2) Add the second aluminum ingot, lower the temperature to 715-725°C, add the second mixed salt and stir to react, raise the temperature, start argon blowing, and the argon flow rate is 70L / min; add the third aluminum ingot to control the temperature of the reaction process not exceeding 760°C, and dump the acid water slag after the reaction is completed;

[0015] 3) Add the fourth aluminum ingot, lower the temperature to 725-730°C, add the third mixed salt and stir to react, raise the temperature, start argon blowing, and the argon flow rate is 70L / min; add the fifth aluminum ingot to control the temperature of the reaction process not exceeding 760°C, the reaction is completed, and the acid water slag is dumped;

[0016] 4) Add the sixth aluminum ingot, lower the temperature to 725-730°C, add the fourth mixed salt, stir and react, raise the temperature, start argon blowing, and the argon flow rate is 70L / min; add the seventh aluminum ingot to control the temperature of the reaction process not exceeding 760°C, the reaction is completed, and the acid water slag is dumped;

[0017] 5) After slag removal, the temperature is raised to 845-850℃, from the converter to the casting furnace, and argon degassing is performed. The argon pressure is 673kpa, the degassing rotor is 250-260Rpm, and the degassing flow rate is 35-45L / min. After degassing, the slag is removed and continuous casting and rolling are carried out.

[0018] The wire rod obtained above is drawn into a desired fineness as required for use as an electrical component.

[0019] The sum of the masses of the first, second, third and fourth salt mixing is equal to the total mass of the mixed salt.

[0020] The sum of the masses of the first aluminum ingot, the second aluminum ingot, the third aluminum ingot, the fourth aluminum ingot, the fifth aluminum ingot, the sixth aluminum ingot and the seventh aluminum ingot is equal to the total mass of the aluminum ingots.

[0021] The above method can effectively inhibit TiAl 3 The particles can improve the electrical conductivity, and the resulting products have excellent high temperature resistance and corrosion resistance.

[0022] In order to further improve the quality of the product, the mass ratio of the first salt mixing, the second salt mixing, the third salt mixing and the fourth salt mixing is: (1-1.06): (1-1.06): (1-1.06): (1-1.06).

[0023] In order to better control product quality, the mass ratio of the first aluminum ingot, the second aluminum ingot, the third aluminum ingot, the fourth aluminum ingot, the fifth aluminum ingot, the sixth aluminum ingot and the seventh aluminum ingot is (0-210): (58-62): (195-300): (58-62): (120-150): (58-62): (120-185).

[0024] In order to improve the uniformity of the product and better control the product quality, in step 1), the first mixing salt addition time is 8-11 minutes, and the reaction time is 5-6 minutes; after adding the first mixing salt, the temperature rises by 18-35°C; and the first aluminum ingot is added to control the reaction process temperature to 735-745°C.

[0025] In order to improve the uniformity of the product and better control the product quality, in step 2), the second salt mixing time is 10-12 minutes, and the reaction time is 3-5 minutes; after adding the second salt mixing, the temperature rises by 10-18°C; and the second aluminum ingot is added to control the reaction process temperature to 744-752°C.

[0026] In order to improve the uniformity of the product and better control the product quality, in step 3), the feeding time of the third mixed salt is 5-6 minutes, and the reaction time is 3-5 minutes; after adding the third mixed salt, the temperature rises by 15-22°C; and the third aluminum ingot is added to control the reaction process temperature to 745-753°C.

[0027] In order to improve the uniformity of the product and better control the product quality, in step 4), the addition time of the fourth mixed salt is 5-6 minutes, and the reaction time is 5-6 minutes; after adding the fourth mixed salt, the temperature rises by 18-24°C; and the fourth aluminum ingot is added to control the reaction process temperature to 745-753°C.

[0028] The above AlTi 4 B 2 The alloy is used as an aluminum base for the preparation of circuit boards or electrical components, not as an intermediate alloy. As an intermediate alloy, TiAl 3 particles, and this application requires the suppression of TiAl 3 of particle.

[0029] The technologies not mentioned in the present invention are all referred to the prior art.

[0030] The present invention AlTi 4 B 2 The alloy has good high temperature resistance, can maintain high strength at high temperatures, is not easy to deform or crack, and has high creep rupture strength, and can maintain structural integrity for a long time; in a high temperature environment, a protective oxide layer can be formed on the surface of the alloy, which effectively prevents further oxidation and carburization, thereby extending the service life of the alloy in extreme environments; strong corrosion resistance: it exhibits good corrosion resistance under strong acid and strong alkali conditions, can resist the erosion of strong acids and alkalis, and maintain the stability of the material; good electrical properties, simple preparation, controllable, and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The electrical components obtained in Example 1 are made of AlTi 4 B 2 Metallographic structure of the alloy (magnification 100x);

[0032] Figure 2 The electrical components obtained in Example 1 are made of AlTi 4 B 2 Metallographic structure of the alloy (magnification 500x);

[0033] Figure 3 The electrical components obtained in Example 2 are made of AlTi 4 B 2 Metallographic structure of the alloy (magnification 100x);

[0034] Figure 4 The electrical components obtained in Example 2 are made of AlTi 4 B 2 Metallographic structure of the alloy (magnification 500x); DETAILED DESCRIPTION

[0035] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0036] Example 1

[0037] First furnace:

[0038] Ingredients:

[0039] Fluoride salt ratio: 380kg potassium borofluoride (KBF4), 350kg potassium fluorotitanate (K2TiF6), mix evenly, mix for 15 minutes. Titanium content in potassium fluorotitanate: 19.5±0.3%, boron content in potassium borofluoride: 8.0-8.7%

[0040] 814kg of molten aluminum and 815kg of aluminum ingots.

[0041] Start of the experiment: At 10:20, molten aluminum was added to the reactor, the temperature of the molten aluminum was 724°C, and the weight of the molten aluminum was 810 kg.

[0042] First feeding reaction: start electromagnetic stirring [300kw], at 10:40, adjust the aluminum liquid temperature, cool it down to 710℃, start adding fluoride salt at 10:45, the mixed salt weight is 180kg, the first feeding is finished at 10:53, the feeding end temperature is 743℃, at 10:59, the reaction is finished, and the acid water slag (potassium fluoroaluminate) is dumped. [Feeding time 8 minutes, reaction time 6 minutes].

[0043] Second feeding reaction: start electromagnetic stirring [power 300kw], add 60kg aluminum ingots to cool down, at 11:06, the temperature dropped to 725℃, start the second addition of mixed salt, the weight of mixed salt is 180kg. Turn on argon blowing, argon flow rate 70L / min; during the mixed salt reaction, add 300kg aluminum ingots to cool down, ensure that the temperature does not exceed 760℃, at 11:18, the second addition of mixed salt ends. The end temperature is 743℃, the reaction ends at 11:24, the end temperature is 752℃, and the acid water slag begins to pour. [Feeding time 12 minutes, reaction 6 minutes].

[0044] The third feeding reaction: start electromagnetic stirring [power 300kw], add 60kg aluminum ingots to cool down, at 11:28, the temperature dropped to 729℃ and started the third addition of mixed salt, adding 180kg. Turn on argon blowing, argon flow rate 70L / min; during the mixed salt reaction, add 150kg aluminum ingots to cool down, ensuring that the temperature does not exceed 760℃, the feeding is finished at 11:34, the end temperature is 748, the reaction is finished at 11:39, the end temperature is 753℃, and the acid water is poured. [Feeding time 6 minutes, reaction time 5 minutes].

[0045] Fourth feeding reaction: start electromagnetic stirring [power 300kw], add 60kg aluminum ingots to cool down, at 11:46, the temperature is 726℃, start the fourth mixed salt reaction, add 190kg, start argon blowing, argon flow rate 70L / min; during the mixed salt reaction, add 185kg aluminum ingots to cool down, ensure that the temperature does not exceed 760℃, 11:54 feeding ends, the end temperature is 745℃. At 11:59, the reaction ends, and acid water pouring begins. After the acid water is poured, 4kg light calcium carbonate is sprinkled on the surface of the aluminum liquid for slag removal, and the slag is removed after the slag removal. [Feeding time 6min, reaction time 5min, acid water pouring time 5min, slag removal time 5min].

[0046] Converter: Started heating at 12:09, after heating to 845℃, at 13:19, the converter was transferred to the casting furnace, and the casting furnace started stirring [power 500kw]. Degassing started at 13:24, and the argon pressure was 673kpa. The degassing rotor was 250Rpm, and the degassing flow rate was 45L / min. Degassing ended at 13:59, and slag removal began. At 14:09, slag removal was completed, and the temperature was raised to prepare for casting. At 14:25, 850℃, continuous casting and rolling began. At 14:36, the hydrogen content was measured: 0.126ml / Al100g. Continuous casting and rolling ended at 14:50. [Continuous casting and rolling time: 25min]. The wire pole.

[0047] The obtained product was tested as follows:

[0048] 1) Composition detection: Ti: 4.08%, B: 1.98%, V: 0.018%, Si: 0.09%, Fe: 0.08%, F: not detected, K: not detected. % are all mass percentages.

[0049] 2) Electrical conductivity: 57% IACS for the first furnace.

[0050] 3) Hydrogen content measurement: 0.126ml / 100gAl.

[0051] 4) Internal cleanliness inspection, such as Figure 1-2 As shown in the figure, the internal structure is uniform and fine, TiB2 Evenly dispersed, average particle size ≤ 2 microns. Total length of oxide < 150μm, no burns, no aggregation and other defects.

[0052] 5) A 10mm*12mm*1mm thin sheet, corroded in 10% NaOH for 100h at room temperature, has a weight loss of 23% of that of 304 stainless steel under the same conditions; corroded in 5% HCl for 100h at room temperature, has a weight loss of 19.8% of that of 304 stainless steel under the same conditions;

[0053] 6) Compared with room temperature (22°C), the strength decay when heated to 300°C is less than 2.1%; the creep rupture strength decay is less than 1.1%.

[0054] Example 2

[0055] Second furnace:

[0056] Ingredients:

[0057] Molten aluminum: 805kg, aluminum ingots: 824kg.

[0058] Mix 350 kg of potassium fluorotitanate and 408 kg of potassium fluoroborate evenly, and mix the salt for 15 minutes.

[0059] Test start: 805 kg of molten aluminum was added at 11:06 and the addition of molten aluminum was completed at 11:25. The final temperature was 740°C;

[0060] First reaction: start electromagnetic stirring [power 300kw], adjust aluminum liquid temperature to 726℃, start adding fluoride salt for the first time at 12:42, end at 12:53, add 190kg of mixed salt, end temperature of adding at 745℃. At 12:58, the first reaction ends, dump the acid water slag. End temperature is 745℃, during which, in order to control the temperature not to exceed 760℃, add 210kg of cooling aluminum ingots; [addition time 11 minutes, reaction time 5 minutes].

[0061] Second reaction: start electromagnetic stirring [power 300kw], add 60kg cooling aluminum ingot, the temperature drops to 718℃, start the second addition of fluoride salt at 13:04, the aluminum liquid temperature is 720℃, the addition ends at 13:14, and the end temperature is 734℃. Add 190kg of fluoride salt, start the second reaction, start argon blowing, argon flow rate 70L / min; the reaction ends at 13:19, and the end temperature is 744℃. During the addition reaction, 194kg cooling aluminum ingots were added to control the aluminum liquid temperature. The acid water slag was dumped at 13:20 and ended at 13:25. [Adding time 10min, reaction time 5min]

[0062] The third reaction: start electromagnetic stirring [power 300kw], add 60kg cooling aluminum ingot, add fluoride salt for the third time at 13:27, temperature 726℃, add 190kg at 13:33, end temperature 746℃. Start the third reaction at 13:34, start argon blowing, argon flow rate 70L / min; end the reaction at 13:39. Add 120kg aluminum ingot to control the temperature during the reaction. Pour acid water at 11:40, temperature 750℃. [Adding time 6min, reaction time 5min]

[0063] The fourth reaction: start electromagnetic stirring [power 300kw], add 60kg aluminum ingot, cool down to 726℃, and start the fourth addition of fluoride salt at 13:44. End at 13:50, add 188kg fluoride salt, and end temperature 749°. Start the fourth reaction at 13:50, start argon blowing, argon flow rate 70L / min; end at 13:55. Add 120kg cooling aluminum ingot during the reaction. 13:56, 751℃, start pouring acid water. End at 14:01, temperature 748℃. 14:02, sprinkle 4.2kg light calcium carbonate on the surface of the aluminum liquid, start slag removal, and end slag removal at 14:06. [Feeding time 6min, reaction time 6min]

[0064] Converter: Started heating at 14:06, started converter at 847℃, started converter at 15:10. Turned on casting furnace power [power 500kw]. Converter ended at 15:25. Degassing started at 15:28, argon pressure 673kpa. Degassing flow 37L / min, degassing rotor 260rpm. Degassing ended at 15:53, started slag removal, ended at 16:01, started continuous casting and rolling at 16:13, temperature 850℃. Continuous casting and rolling ended at 16:39. [Casting and rolling time 26min]. The wire pole.

[0065] The obtained product was tested as follows:

[0066] 1) Composition detection: Ti: 4.12%, B: 1.97%, V: 0.018%, Si: 0.10%, Fe: 0.09%, F: not detected, K: not detected. % are all mass percentages.

[0067] 2) Electrical conductivity: 59% IACS for the second furnace.

[0068] 3) Hydrogen content measurement: 0.122ml / 100gAl.

[0069] 4) Internal cleanliness inspection, such as Figure 3-4 As shown in the figure, the internal structure is uniform and fine, TiB 2Uniform dispersion, average particle size ≤ 2μm, total oxide length <150μm, no burns, no aggregation and other defects.

[0070] 5) A 10mm*12mm*1mm thin sheet, corroded in 10% NaOH for 100h at room temperature, has a weight loss of 20.3% of that of 304 stainless steel under the same conditions; corroded in 5% HCl for 100h at room temperature, has a weight loss of 16.8% of that of 304 stainless steel under the same conditions;

[0071] 6) Compared with room temperature (22°C), the strength decay when heated to 300°C is less than 1.9%; the creep rupture strength decay is less than 1.0%.

[0072] Comparative Example 1

[0073] The difference from Example 1 is that the amount of potassium fluorotitanate is 450 kg, and the amount of salt added in the four mixings is 205 kg, 205 kg, 205 kg, and 215 kg respectively. The rest is the same as Example 1. The total length of the oxide is greater than 1500 μm. The corrosion weight loss in 10% NaOH and 5% HCl exceeds that of 304 stainless steel; compared with room temperature (22°C), the strength decay is 19.6% when heated to 300°C; the creep rupture strength decay is 16.5%.

[0074] Comparative Example 2

[0075] The difference from Example 1 is that the amount of potassium fluorotitanate is 250 kg, and the amount of salt added in the four mixing times is 155 kg, 155 kg, 155 kg, and 165 kg respectively. The rest is the same as Example 1. The total length of the oxide is greater than 1500 μm. The corrosion weight loss in 10% NaOH and 5% HCl exceeds that of 304 stainless steel; compared with room temperature (22°C), the strength decay is 22.3% when heated to 300°C; the creep rupture strength decay is 20.1%.

[0076] Comparative Example 3

[0077] The difference from Example 1 is that the amount of molten aluminum is 714 kg, and the rest is the same as Example 1. The corrosion in 10% NaOH is equivalent to that of 304 stainless steel, and the corrosion loss in 5% HCl is greater than that of 304 stainless steel; compared with room temperature (22°C), the strength decay is 16.7% when heated to 300°C; and the creep rupture strength decay is 15.2%.

[0078] Comparative Example 4

[0079] The difference from Example 1 is that the amount of aluminum liquid is 914 kg, and the rest is the same as Example 1. The corrosion weight loss in 10% NaOH and 5% HCl exceeds that of 304 stainless steel; compared with room temperature (22°C), the strength decay is 19.2% when heated to 300°C; and the creep rupture strength decay is 17.9%.

[0080] Comparative Example 5

[0081] The difference from Example 1 is that the mixed salt is added once for 32 minutes, and then reacted for 22 minutes, and the rest is the same as Example 1. The total length of the oxide is greater than 2500 μm. Compared with room temperature (22°C), the strength decay is 23.7% when heated to 300°C; the creep rupture strength decay is 22.1%.

[0082] The intergranular corrosion test of each case is shown in the following table (GB / T 7998-2005 "Determination method of intergranular corrosion of aluminum alloy").

[0083]

Claims

1. An AlTi4B2 alloy for electrical components, characterized in that: The composition comprises the following elements: Ti: 3.9-4.2%; B: 1.9-2.1%; Si≤0.15%; Fe≤0.1%; K≤0.05%; F≤0.02%; V≤0.02%; Al: balance, the aforementioned % are all mass percentages.

2. The AlTi4B2 alloy for electrical components according to claim 1, characterized in that: The raw materials used include: potassium fluoroborate, potassium fluorotitanate, aluminum water and aluminum ingot; the mass ratio of potassium fluoroborate, potassium fluorotitanate, aluminum water and aluminum ingot is: (340-390): (350-410): (800-820): (810-830).

3. A method for preparing the AlTi4B2 alloy for electrical components according to claim 1 or 2, characterized in that: Potassium fluoroborate and potassium fluorotitanate are mixed evenly to obtain mixed salt; the mixed salt is added in four times, and the aluminum ingot is added in seven times. The specific process is as follows; 1) Adjust the temperature of aluminum water to 710-730°C, add the first mixed salt to stir and react, increase the temperature, add the first aluminum ingot to control the temperature of the reaction process not exceeding 760°C, and dump the acid water slag after the reaction is completed; 2) Add the second aluminum ingot, lower the temperature to 715-725°C, add the second mixed salt and stir to react, raise the temperature, start argon blowing, and the argon flow rate is 70L / min; add the third aluminum ingot to control the temperature of the reaction process not exceeding 760°C, and dump the acid water slag after the reaction is completed; 3) Add the fourth aluminum ingot, lower the temperature to 725-730°C, add the third mixed salt and stir to react, raise the temperature, start argon blowing, and the argon flow rate is 70L / min; add the fifth aluminum ingot to control the temperature of the reaction process not exceeding 760°C, the reaction is completed, and the acid water slag is dumped; 4) Add the sixth aluminum ingot, lower the temperature to 725-730°C, add the fourth mixed salt, stir and react, raise the temperature, start argon blowing, and the argon flow rate is 70L / min; add the seventh aluminum ingot to control the temperature of the reaction process not exceeding 760°C, the reaction is completed, and the acid water slag is dumped; 5) After slag removal, the temperature is raised to 845-850℃, from the converter to the casting furnace, and argon degassing is performed. The argon pressure is 673kpa, the degassing rotor is 250-260Rpm, and the degassing flow rate is 35-45L / min. After degassing, the slag is removed and continuous casting and rolling are carried out.

4. The method for preparing the AlTi4B2 alloy for electrical components according to claim 3, characterized in that: The mass ratio of the first salt mixing, the second salt mixing, the third salt mixing and the fourth salt mixing is: (1-1.06): (1-1.06): (1-1.06): (1-1.06).

5. The method for preparing the AlTi4B2 alloy for electrical components according to claim 3 or 4, characterized in that: The mass ratio of the first aluminum ingot, the second aluminum ingot, the third aluminum ingot, the fourth aluminum ingot, the fifth aluminum ingot, the sixth aluminum ingot and the seventh aluminum ingot is (0-210): (58-62): (195-300): (58-62): (120-150): (58-62): (120-185).

6. The method for preparing the AlTi4B2 alloy for electrical components according to claim 3 or 4, characterized in that: In step 1), the first addition time of the mixed salt is 8-11 minutes, and the reaction time is 5-6 minutes; after the first addition of the mixed salt, the temperature rises by 18-35° C.; the first addition of the aluminum ingot controls the temperature of the reaction process to be 735-745° C.

7. The method for preparing the AlTi4B2 alloy for electrical components according to claim 3 or 4, characterized in that: In step 2), the second addition time of the mixed salt is 10-12 minutes, and the reaction time is 3-5 minutes; after the second addition of the mixed salt, the temperature rises by 10-18°C; the second addition of the aluminum ingot controls the temperature of the reaction process to be 744-752°C.

8. The method for preparing the AlTi4B2 alloy for electrical components according to claim 3 or 4, characterized in that: In step 3), the third addition time of the mixed salt is 5-6 minutes, and the reaction time is 3-5 minutes; after the third addition of the mixed salt, the temperature rises by 15-22°C; the third addition of the aluminum ingot controls the temperature of the reaction process to be 745-753°C.

9. The method for preparing the AlTi4B2 alloy for electrical components according to claim 3 or 4, characterized in that: In step 4), the adding time of the fourth mixed salt is 5-6 minutes, and the reaction time is 5-6 minutes; after adding the fourth mixed salt, the temperature rises by 18-24°C; and the fourth aluminum ingot is added to control the reaction process temperature to 745-753°C.

10. Use of the AlTi4B2 alloy for electrical components according to claim 1 or 2, characterized in that: Used for the preparation of circuit boards or electrical components.